Hardening foreign corporate accountability through mandatory due diligence in the European Union? New trends and persisting challenges - Schilling-Vacaflor, Almut; Lenschow, Andrea (Regulation & Governance, 2023)
The negative externalities of global commodity chains and existing governance gaps have received wide scholarly attention. Indeed, many sectors including forest-risk commodities (FRCs) like soy and beef from Brazil remain largely unregulated. This article analyzes ongoing policy-making processes at European Union level to adopt new regulations for reducing accountability gaps: one regulation of FRCs and one general, cross-sectoral directive on human rights and environmental due diligence. This article draws on and aims to contribute to previous research into foreign corporate accountability, therein analytically distinguishing between input, output, and surrogate accountability. This study shows that new policies will likely be more comprehensive than previous supply chain regulations, while their specific institutional design and stringency are highly contested. More in general, we argue that for hardening corporate accountability, due diligence politics will need to confront important governance challenges that have limited the potential of previous regulations, such as a lack of consequentiality of reporting obligations, weak state monitoring, limited stakeholder involvement, and difficulties to establish legal liability.
CRIS-Team Scopus Importer:2023-11-20
Keywords: Brazil; commodity chain; deforestation; European Union (EU); human rights